Pengaruh Model Pembelajaran Misouri Mathematics Project (MMP) Dalam Meningkatkan Prestasi Belajar Siswa SD Kelas V - Lalu Jaswandi (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2023)
Abstract (English)Learning achievement is a teaching goal that is expected of all students. To support the achievement of these teaching objectives, it is necessary to have teaching and learning activities that involve students, teachers, subject matter, teaching methods, curriculum and learning media that suit the needs of students and are supported by a conducive teaching and learning environment. Data analysis techniques in this study used the t-test, namely to see the effect of the Misouri Mathematics Project (MMP) learning model in improving learning achievement. Before the t-test is carried out, the hypothesis testing requirements are first tested, namely the data is first tested by the population using the normality test and homogeneity test. The t-test in this study was carried out using the SPSS program for a significant level a = 5% = 0.05. Student responses to the application of the Missouri Mathematics Project learning model in learning activities are included in the positive response category. The use of the Missouri Mathematics Project learning model can increase students' learning achievement in mathematics. This can be seen from the results of the hypothesis test which shows that the value of thitung> ttabel, then H0 is rejected, meaning that there is a significant effect of using the Missouri Mathematics Project learning model on improving students' mathematics learning achievement.Key Words: misouri mathematics project, Learning achievementAbstrak (Indonesia)Prestasi belajar merupakan tujuan pengajaran yang diharapkan semua peserta didik. Untuk menunjang tercapainya tujuan pengajaran tersebut perlu adanya kegiatan belajar mengajar yang melibatkan siswa, guru, materi pelajaran, metode pengajaran, kurikulum dan media pembelajaran yang sesuai dengan kebutuhan siswa serta didukung oleh lingkungan belajar-mengajar yang kondusif. Teknis analisis data dalam penelitian menggunakan uji-t yaitu untuk melihat pengaruh model pembelajaran misouri mathematics project (MMP) dalam meningkatkan prestasi belajar. Sebelum dilakukan uji-t terlebih dahulu dilakukan uji persyaratan pengujian hipotesis adalah data terlebih dahulu dilakukan pengujian populasi dengan menggunakan uji normalitas dan uji homogenitas. Uji-t dalam penenlitian ini dilakukan dengan program SPSS untuk taraf signifikan a = 5% = 0,05. Respon siswa terhadap penerapan model pembelajaran Missouri Mathematics Project dalam kegiatan pembelajaran termasuk kategori respon positif. Penggunaan model pembelajaran Missouri Mathematics Project dapat meningkat prestasi belajar matematika siswa. Hal ini terlihat dari hasil uji hipotesis yang menunjukkan bahwa nilai thitung > ttabel maka H0 ditolak artinya terdapat pengaruh yang signifikan penggunaan model pembelajaran Missouri Mathematics Project terhadap peningkatan prestasi belajar matematika siswa.Kata Kunci: misouri mathematics project, Prestasi Belajar